Post-inflammatory Ileitis Induces Non-neuronal Purinergic Signaling Adjustments of Cholinergic Neurotransmission in the Myenteric Plexus - Cátia Vieira; Fátima Ferreirinha; Maria T. Magalhães-Cardoso; Isabel Silva; Patrícia Marques; Paulo Correia- (Frontiers Media S.A., 2017)
Uncoupling between ATP overflow and extracellular adenosine formation changes purinergic signaling in post-inflammatory ileitis. Adenosine neuromodulation deficits were ascribed to feed-forward inhibition of ecto-5'-nucleotidase/CD73 by high extracellular adenine nucleotides in the inflamed ileum. Here, we hypothesized that inflammation-induced changes in cellular density may also account to unbalance the release of purines and their influence on [3H]acetylcholine release from longitudinal muscle-myenteric plexus preparations of the ileum of 2,4,6-trinitrobenzenesulfonic acid (TNBS)-treated rats. The population of S100β-positive glial cells increase, whereas Ano-1-positive interstitial cells of Cajal (ICCs) diminished, in the ileum 7-days after the inflammatory insult. In the absence of changes in the density of VAChT-positive cholinergic nerves detected by immunofluorescence confocal microscopy, the inflamed myenteric plexus released smaller amounts of [3H]acetylcholine which also became less sensitive to neuronal blockade by tetrodotoxin (1 μM). Instead, [3H]acetylcholine release was attenuated by sodium fluoroacetate (5 mM), carbenoxolone (10 μM) and A438079 (3 μM), which prevent activation of glial cells, pannexin-1 hemichannels and P2X7 receptors, respectively. Sodium fluoroacetate also decreased ATP overflow without significantly affecting the extracellular adenosine levels, thus indicating that surplus ATP release parallels reactive gliosis in post-inflammatory ileitis. Conversely, loss of ICCs may explain the lower amounts of adenosine detected in TNBS-treated preparations, since blockade of Cav3 (T-type) channels existing in ICCs with mibefradil (3 μM) or inhibition of the equilibrative nucleoside transporter 1 with dipyridamole (0.5 μM), both decreased extracellular adenosine. Data indicate that post-inflammatory ileitis operates a shift on purinergic neuromodulation reflecting the upregulation of ATP-releasing enteric glial cells and the depletion of ICCs accounting for decreased adenosine overflow via equilibrative nucleoside transporters.